Dentin microhardness during and after whitening treatments - Freitas, P. M. de; Turssi, C. P.; Hara, A. T.; Serra, M. C. (Quintessence Publ Co Inc, 2004)
Objective: This in vitro study aimed to evaluate the effect of bleaching agents on dentin microhardness during and after bleaching. Method and materials: Specimens were randomly assigned to seven groups (n = 15): Nite White Excel 2 Z [NW] 10% and 22%; Rembrandt [REM] 10% and 22%; Opalescence [OPA] 10% and 20%; and a placebo agent. The 42-day whitening treatment consisted of daily application of the agents to the dentin surfaces for 8 hours, followed by immersion in artificial saliva for 16 hours. After the bleaching treatment, specimens were kept immersed in artificial saliva for 14 days. Microhardness was measured at baseline, 8 hours, and 7, 14, 21, 28, 35, and 42 days of bleaching and during the posttreatment period (7 and 14 days). Results: The analysis of variance for split-plot showed a significant effect on the interaction between bleaching agent and time. Tukey's test and regression analyses revealed that during the bleaching period, the agents NW 10%, NW 22%, and OPA 20%, which did not differ from each other, did not alter dentin microhardness, showing constant microhardness values. There were no differences among REM 10%, REM 22%, and OPA 10%, which showed significant reductions in microhardness after day 14 compared to other agents. After bleaching procedures, there was an increase in dentin microhardness for all groups. Conclusion: Throughout the bleaching treatment, depending on the agent applied, dentin showed a transitory decrease in microhardness values. In the posttreatment period, artificial saliva presented a remineralizing effect on the bleached surfaces.
Keywords: bleaching; carbamide peroxide; dentin; microhardness; saliva; vital teeth